A Content Analysis of Experimental Technologies in Award-Winning Creative Strategies. Issue 2 (2nd July 2016) - Qiao, Fei; Griffin, W. Glenn
ABSTRACT: Experimental technologies are defined as technologies that were not originally developed to help create or deliver advertising messages but are employed to do so. Drawing upon the conceptual model of creativity and DDB Worldwide's "ROI of creativity, " award-winning creative strategies that incorporate experimental technologies are categorized as affective or reactive to describe the type of consumer response they are intended to elicit. A total of 82 award-winning creative strategies were analyzed. Findings suggest that experimental technologies are more often incorporated in award-winning strategies for non-technology-related products than other categories. In addition, award-winning strategies incorporating experimental technologies appear more likely to elicit affective consumer responses. Theoretical and practical implications of these findings are discussed.